The Public Perception of Islamic Education at Wali Songo Islamic Boarding School Sukajadi Village, Bumiratu Nuban District - Ulum, Syaikhul; Mispani, Mispani; Jaenullah, Jaenullah; Thohir, Muhyidin (Bulletin of Pedagogical Research, 2021)
Islamic Boarding School is a religious institution that cannot be separated from the community. This institution grows and develops for the community by positioning itself as part of the community. Along with the times, the demands of society towards the world of islamic boarding school have indeed been developing rapidly, especially in terms of education. At this time the islamic boarding school is started to be in great demand by most parents and the public who want more things than the existence of a boarding school. As for the needs and demands of the community towards Islamic Boarding School, santri must possess intellectual, spiritual intelligence and religious skills. This Research used qualitative methods with a descriptive quantitative approach. The determination of data sources is based on the theory of snow ball sampling. Data collecting techniques used documentation, observation and interviews. Data analysis techniques used data reduction, data presentation and drawing conclusions. To test the validity of the data used the triangulation method. The results of research show that Public perception of islamic boarding school in education is good. This can be seen through the significant increase of the students number, the development of curriculum that is oriented towards the development of intellectual and spiritual intelligence. The demands and needs of the public towards Islamic boarding schools are students having skills in religious fields such as: recitations, da'i, imam yasin, and khotib. In addition to the guidance, the public also demanded that students be able to speak foreign languages and to operate computers for the future. The effort undertaken by the Islamic boarding school is to compile a curriculum for madrasa dinniyah by incorporating a number of disciplines, conducting muhadorh, barzanji, yasin and tahlil activities to hone the ability of students in the religious field. Keywords: Islamic Education, Islamic Boarding School, Pesantren Wali Songo